AVALIAÇÃO DE FATORES ASSOCIADOS AO USO DE BENZODIAZEPÍNICOS EM IDOSOS - Márcia Raquel Venturini Baggio (2022)
Introduction: Assistance to the elderly population demands knowledge of the particularities of the senescence and senile aging process. Multimorbidity and polypharmacy are just a few of the greatest challenges in care practice. Benzodiazepines (BZD) are sedative drugs frequently used in the elderly population, although their use is associated with cognitive impairment and faster progression to dementia, making these agents less suitable for this population. Additionally, the adoption of drugs that depress the nervous activity in an already fragile population with frequent polypharmacy increases the risks of drug interactions, prescription cascades, and iatrogenesis. Objectives: To evaluate factors associated with the use of benzodiazepines by the elderly in Primary Health Care in the city of Ilha Solteira/SP. Methods: This is a cross-sectional and quantitative study, with primary and secondary data collection, carried out with the elderly population assigned to the 10 family health teams in the municipality of Ilha Solteira/SP (n=144), between March and November 2021. The study was carried out with two groups of elderly people, grouping those who use BZD (n=72) and those who do not use these drugs (control; n=72). Socioeconomic parameters, health aspects, and patterns of medication use were evaluated. In the BZD group, parameters related to the pattern of consumption of these drugs were evaluated. Dependence and independence were assessed by applying the Instrumental Activities of Daily Living and Basic Activities of Daily Living scales. The research was approved by the Research Ethics Committee/UFMS (CAAE 42983421.8.0000.0021, opinion 4.605.400). Results: Factors associated with the use of BZD by the elderly were: female gender and lower average monthly family income; performing physical activities less frequently or not performing at all; higher prevalence of chronic diseases, especially hypothyroidism; greater occurrence of constipation and falls, cognitive impairment and/or memory loss and worsening of depression symptoms in the last 12 months; higher prevalence of polypharmacy, with an increase in the number of drugs used in the past 12 months, especially drugs to control gastric acidity, vitamins, mineral supplements, thyroid hormones, antiepileptics, antidepressants, anxiolytics and sedatives; Use of potentially inappropriate drugs in greater frequency and number, and; higher scores associated with the anticholinergic activity imposed by the drug treatment used. The elderly that used BZD presented a chronic pattern of drug use, especially clonazepam, for treating insomnia, with reported side effects and associated additional complaints. Almost 25% of the elderly using BZD also used other drugs with important potential drug interactions. Conclusion: Although the use of BZD by elderly patients is contraindicated by most clinical guidelines, it is still possible to observe the pattern of consumption by patients over 60 years of age. The negative consequences associated with the treatment using these drugs require attention, especially considering the deterioration of general health status and worse prognosis in elderly patients.